A multi-user process interface system for a process control computer - Sherlock, Barry Graham (Department of Electrical Engineering, 2023)
This thesis describes a system to implement a distributed multi-user process interface to allow the PDP-11/23 computer in the Electrical Engineering department at UCT to be used for process control. The use of this system is to be shared between postgraduate students for research and undergraduates for doing real-time control projects. The interface may be used concurrently by several users, and access is controlled in such a way as to prevent users' programs from interfering with one another. The process interface hardware used was a GEC Micro-Media system, which is a stand-alone process interface system communicating with a host (the PDP-11/23) via a serial line. Hardware to drive a 600-metre serial link at 9600 baud between the PDP-11/23 and the Media interface was designed and built. The software system on the host, written in RTL/2, holds-all data from the interface in a resident common data-base and continually updates it. Access to the interface by applications programs is done indirectly by reading and writing to the database, for which purpose a library of user interface routines is provided. To allow future expansion and modification of the Media interface, software (also written in RTL/2) for an LSI-11 minicomputer interfaced to the Media bus was developed which emulates the operation of the GEC proprietary Micro-Media software. A program to download this software into the LSI-11 was written. A suite of diagnostic programs enables testing of the system hardware and software at various levels. To ease testing, teaching, and applications programming, a general-purpose simulation package for the simulation of analogue systems was developed, as well as graphics routines for use with a Tektronix 4010 plotting terminal. A. real-time computing project for a class of undergraduates was run in 1983. This project made extensive use of the system and demonstrated its viability.